Mapping of phosphorylation sites in polyomavirus large T antigen. - Hassauer, M (1986)
The phosphorylation sites of polyomavirus large T antigen from infected or transformed cells were investigated. Tryptic digestion of large T antigen from infected, 32Pi-labeled cells revealed seven major phosphopeptides. Five of these were phosphorylated only at serine residues, and two were phosphorylated at serine and threonine residues. The overall ratio of phosphoserine to phosphothreonine was 6:1. The transformed cell line B4 expressed two polyomavirus-specific phosphoproteins: large T antigen, which was only weakly phosphorylated, and a truncated form of large T antigen of 34,000 molecular weight which was heavily phosphorylated. Both showed phosphorylation patterns similar to that of large T antigen from infected cells. Peptide analyses of large T antigens encoded by the deletion mutants dl8 and dl23 or of specific fragments of wild-type large T antigen indicated that the phosphorylation sites are located in an amino-terminal region upstream of residue 194. The amino acid composition of the phosphopeptides as revealed by differential labeling with various amino acids indicated that several phosphopeptides contain overlapping sequences and that all phosphorylation sites are located in four tryptic peptides derived from a region between Met71 and Arg191. Two of the potential phosphorylation sites were identified as Ser81 and Thr187. The possible role of this modification of large T antigen is discussed.